2004
DOI: 10.1158/0008-5472.can-03-2858
|View full text |Cite
|
Sign up to set email alerts
|

Cullin 3 Promotes Proteasomal Degradation of the Topoisomerase I-DNA Covalent Complex

Abstract: DNA topoisomerase I (TOP1)-DNA covalent complexes are the initial lesions produced by antitumor camptothecins (CPTs). The TOP1-directed drugs stimulate degradation of TOP1 via the ubiquitin-proteasome pathway. We found that proteasome inhibition prevents degradation of DNAbound TOP1 and sustains high levels of covalent complexes, thus enhancing CPT-induced cell death. Consistent with this, increased degradation of TOP1-DNA covalent complexes was seen in acquired CPT-resistant cells. We found that the resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 36 publications
(41 reference statements)
5
39
0
Order By: Relevance
“…The decreased expression of CA IX in the posttreatment tumors is consistent with the inhibitor effect of CRLX101 on HIF-1α expression, which has been previously observed (7,15). CPT has been known to cause rapid degradation of Topo-I through the ubiquitin-proteasome system in tissue culture (16)(17)(18)(19)(20). Our result reveals this may also be occurring in vivo as evident by the lower staining of Topo-I in the posttreatment tumors.…”
Section: Discussionsupporting
confidence: 89%
“…The decreased expression of CA IX in the posttreatment tumors is consistent with the inhibitor effect of CRLX101 on HIF-1α expression, which has been previously observed (7,15). CPT has been known to cause rapid degradation of Topo-I through the ubiquitin-proteasome system in tissue culture (16)(17)(18)(19)(20). Our result reveals this may also be occurring in vivo as evident by the lower staining of Topo-I in the posttreatment tumors.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it has been suggested that the Top1 must undergo proteolysis in order for efficient Tdp1 activity [19,41,45], which is in agreement with studies demonstrating that the effectiveness of Tdp1 processing decreases as the length of the Top1 polypeptide is extended [45]. Accordingly, several studies have shown that Top1 is degraded in some cells lines following CPT treatment, suggesting that Top1 ubiquitination and degradation contribute to CPT resistance [46][47][48][49]. In addition, prevention of Top1 degradation by the proteasome inhibitors, MG132 [47] or PS-341 (clinically used) [50], results in increased sensitivity to CPT.…”
Section: Tdp1 Substratessupporting
confidence: 54%
“…Indeed, cells proficient in this repair process are more resistant to CPT (7). In addition, overexpression of Cullin3, a component of a SCF complex, has been shown to increase ubiquitination and TOP1 down-regulation, resulting in CPT resistance (16). Furthermore, cotreatment with the proteasome inhibitor, MG132, which inhibits TOP1 down-regulation, increases tumor cell sensitivity to CPT (7).…”
Section: Introductionmentioning
confidence: 99%